Idealisme Kekristenan Dalam Konteks Moderasi Beragama (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Christian idealism has a striking and identical nature in terms of its radicalism when associated with religion, especially Christianity. It can be clearly seen that idealism is one of the ideologies that if associated with religion provides a program or method that is different from the usual in the sense of providing a deep appreciation of religious understanding. Although it is a difficult thing to change in general, idealism seeks to proclaim renewal to find the right solution to the case study factors in human life that will continue progressively, to find the eternity of the real truth of religion itself. The combination of the nature of Christianity with idealism can certainly complement each other if each other balances and harmonizes in the teaching of the living and true truth of the absolute truth of God's word, so that it will have a major positive impact on mankind.